The Role of Nutrition in Preventing Developmental and Cognitive Problems in Early Childhood: A Neuroscience Perspective - Izza Ikromatus Sa'adah; Khuliyatul Nusroh; Novida Riasti; Aisya Mashadi; Rachma Hasibuan (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Early childhood is a critical period for brain and cognitive development, which is strongly influenced by nutritional factors. This article aims to examine the role of nutrition in preventing developmental and cognitive problems in young children from a neuroscience perspective. Using the Systematic Literature Review (SLR) method, this study reviewed ten scientific articles from various reliable sources published between 2007 and 2025. The findings indicate that adequate nutritional intake—particularly iron, iodine, omega-3 fatty acids, and B-complex vitamins—has a significant impact on brain structure and function as well as children’s cognitive abilities. Family conditions and dietary diversity also play an important role in neurological development. In addition, interactions between nutrition, physical activity, and gut microbiota emerge as relevant recent findings in supporting brain health. This article concludes that early nutritional interventions should be a primary focus of child health and education policies and must be supported by multisectoral approaches to foster a healthy, intelligent, and productive generation.